Development of Agaricus bisporus cultivation in Brazil: Compost supplementation and use of hybrid strains - Zied, Diego Cunha [UNESP]; Pardo, Jose Emilio [UNESP]; Álvarez-Ortí, M. Manuel; Pardo-Giménez, Arturo (GN1 Sistemas e Publicacoes, 2018)
The use of hybrids strains of known origin in mushroom cultivation is not very common in Brazil. Likewise, the practice of supplementation of compost is not applied. Supplementation of compost in mushroom cultivation consists in the addition at the end of Phase II composting process. The aim of the research is the evaluation of two doses of a commercial supplement of nutritious substances in two different hybrid mushroom strains. Two crop cycles were conducted. Yields are positively affected as a result of supplementation, significantly with the smooth white hybrid strain. This strain provides more fruiting bodies and higher yields than the large off-white hybrid type, but showed smaller mushrooms. Qualitative production parameters are not affected as a result of supplementation. This practice leads to moderate increases in the temperature of the compost during the vegetative growth phase. The results confirm the interest of supplementing the compost in order to improve the productivity.
Desarrollo del cultivo de Agaricus bisporus en Brasil: Suplementación del compost y utilización de híbridos
Keywords: Agaricus bisporus; Quality; Spawn; Supplements; Yield